Physicians' Perspective on Reproductive Health Education [9R]. (May 2018) - Do, Linh; Reddy, Sireesha
Abstract : INTRODUCTION: Reproductive health education (RHE) to adolescents is essential to decreasing teen pregnancy rates, increasing contraceptive use and overall knowledge of reproductive health. We are interested in learning physicians' perspective on RH topics, what age is appropriate for the discussions and on parental presence during RHE discussions. METHODS: A 20-question survey with inclusion criteria, demographics, and subjective norm concerning 9 RHE topics such as puberty, period, STI, pregnancy, contraception, sex, HIV/AIDS, abortion, and gender identity and sexual orientation were inputted on RED CAP. An individualized link was emailed to 123 pediatric, Obstetrician & Gynecologist, and family physicians at Texas Tech University Health Center. 42 surveys completed. RESULTS: Physicians believe parents should be in the room during RHE discussions with a P<.05% with a 32% response rate. Significantly more Obstetrician & Gynecologist prefer to discuss contraceptive use with parental presence out of the 9 RHE topics for both male and female adolescents compared to pediatricians. Physician parental status does not affect their opinion on parental attendance during this conversation. CONCLUSION: OBGYN, pediatricians and family medicine doctors desire parent presence when discussing RHE topics. This may be for fear of what parents may think about certain topics. However, confidentiality is also a concern. Physicians need more counselling that parents and their adolescents desire confidentiality. Our previous survey showed that dependent on topic and age, confidentiality and sole discussions can be appropriate.